2021
DOI: 10.18196/jmmr.v10i1.10376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of workforce requirements based on WISN in radiology installation of RSU X

Abstract: The beginning of 2020 was shocked by the WHO's statement which mentioned Coronavirus-19 (COVID-19) as a pandemic. As many as 37420 confirmed cases of COVID-19 were reported by the Ministry of Health of the Republic of Indonesia until June 2020 and are growing every day. One of the supporting examinations to establish a diagnosis of COVID-19 is a radiological examination. It is undeniable that the increasing incidence of COVID-19 has caused the workload of health workers in hospitals is increase, including in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The working components that affected this factor included nursing audit meetings, preparation of medicines and equipment, preparation of consumables, and reporting. The category allowance factor in this study was smaller than in previous studies that showed category allowance factors of 0.183 and 0.39 (Ekawati 2018, Farrasizdihar et al 2021. The small category allowance factor in this study might be because there were not many activities conducted outside of the Hemodialysis Unit of Rasyida Renal Specialist Hospital.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The working components that affected this factor included nursing audit meetings, preparation of medicines and equipment, preparation of consumables, and reporting. The category allowance factor in this study was smaller than in previous studies that showed category allowance factors of 0.183 and 0.39 (Ekawati 2018, Farrasizdihar et al 2021. The small category allowance factor in this study might be because there were not many activities conducted outside of the Hemodialysis Unit of Rasyida Renal Specialist Hospital.…”
Section: Discussioncontrasting
confidence: 73%
“…This study showed that nursing activities in the Hemodialysis Unit were quite busy. There were similarities between this study and another study conducted in a radiology unit where nurses spent more time on directly and indirectly productive care activities compared to non-productive activities (Farrasizdihar et al 2021). Productive activities are the main activities in nurses' duties and responsibilities.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations